A passively adaptive variable-radius pulley for a tendon-driven robotic joint. (October 2018) - Park, Jihyuk; Kim, Ji-Chul; Nguyen, Chanh D.Tr.; Kim, Kyung-Soo; Kim, Soohyun
Highlights: A novel concept for a variable-radius pulley that passively changes its transmission ratio as a function of the external load is proposed. The mechanism is based on the face cam mechanism and bi-directional stiffness mechanism. The proposed variable-radius pulley is a simple and lightweight system, whereas many conventional transmission systems are heavy and complex, with additional actuators. It is possible to directly apply the pulley to current tendon-based robot platforms instead of developing new robot platforms to apply the proposed idea. Abstract: This paper presents the concept of and a design method for a new variable-radius pulley that passively changes the effective radius of a driven pulley in a belt-driven transmission in response to a changing load torque. The proposed mechanism is based on the principle that the effective radius of the pulley is passively increased when a torque is applied to the pulley by means of a cam element and an elastic element. In a belt-driven transmission, the radial size of the driven pulley determines the relationship between the output torque and the output speed. Whereas a belt-driven transmission with a typical pulley of constant radius has a fixed maximum speed and torque, a variable-radius pulley allows the maximum speed and torque to vary, enabling more efficient driving. This paper describes the working principle of the new variable-radius pulley and presents a static analysis of the proposed mechanism. Simulations and experiments conducted to demonstrate the proposed mechanism are reported, and the results show that the proposed variable-radius pulley can be used to vary the transmission ratio in accordance with the torque applied to the robot joint.